AB0006 A Genome-Wide Association Study for Methotrexate-Induced Pneumonitis in Rheumatoid Arthritis. (9th June 2015) - Bluett, J.; Owens, S.-A.; Massey, J.; Plant, D.; Verstappen, S.; Barton, A.
Abstract : Background: Whilst methotrexate (MTX) is the first-line treatment for rheumatoid arthritis (RA), it is associated with a rare but potentially life-threatening lung disease, MTX-pneumonitis (MTX-P). Epidemiological studies have provided evidence that MTX-P may be a genetically susceptible disease, supported by the fact that the incidence is much higher in the Japanese population than Europeans. Clinical risk factors are associated with the development of MTX-P; they are however, poorly predictive, there is therefore a need for improved markers of disease susceptibility. To date, only one locus has been associated with MTX-P in the Japanese population (HLA-A 31:01). Objectives: To undertake a genome-wide association study (GWAS) for MTX-P in RA to identify genetic predictors of this rare adverse event. Methods: Cases of MTX-P were recruited from a UK-wide multi-centre study. Cases were physician diagnosed MTX-P. Controls were recruited from the Rheumatoid Arthritis Medications Study (RAMS), a multi-centre observational study in the UK. Controls were participants with RA taking MTX for at least 1 year without the development of MTX-P and were age:sex matched 3:1 to cases. Results: 65 cases and 195 controls were recruited. The study has an 80% power to detect an allele with frequency 0.30 and allelic odds ratio of 3.0. Samples were genotyped on the Illumina HumanCoreExome chip. Following quality control, 62 cases and 172 controls remained with coverage of 236308 SNPs. 48 cases (77%) retrospectively fulfilled either the Carson et al. or Searles et al. unvalidated criteria for MTX-P. 3 SNPs were associated with MTX-P at P< 10 -5, rs6593803 ( p =1.85 X 10 -7, OR =3.13) maps near GJA5, rs9299346 ( p =1.76 X 10 -6, OR =2.76) in GRIN3A and rs1624005 ( p =6.54 X 10 -6, OR =2.59) maps near LRFN5 . No SNPs reached genome-wide significance. Conclusions: 3 SNPs were associated with MTX-P at borderline significance levels. These findings need further corroboration in replication studies. References: Ann Rheum Dis 2013;72(1):153-5. Disclosure of Interest: None declared